Literacy Program-Based Financing Model in Improving Learning Quality - H. Soro , Suharyanto; Meliyanti, Meliyanti; Nurhasanah, Nurhasanah; Intan, Intan (Global Education Journal, 2025)
Improving the quality of learning at the elementary school level cannot be separated from the success of literacy programs supported by planned and sustainable funding. The implementation of literacy programs is hampered by suboptimal funding factors. This study aims to describe and analyze the literacy program-based funding model implemented at SDN Sirnagalih, Bandung Regency. Using a case study approach. Data were collected through observation, interviews, and documentation which were then analyzed using the Miles and Huberman techniques. The results of the study indicate that the funding model is implemented through the POAC ( Planning, Organizing, Actuating, Controlling ) strategy with the support of a 10% BOS fund allocation for literacy programs. Programs such as 'Selasa Literasi', 'Pojok Baca', and 'Sedekah Buku' have shown real contributions to improving students' literacy skills. These findings provide practical implications for education managers to design budget policies based on program needs. In conclusion, proper funding management contributes significantly to improving the quality of literacy-based learning.